2008
DOI: 10.1108/14626000810871709
|View full text |Cite
|
Sign up to set email alerts
|

Are misalignments of perceptions and self‐efficacy causing gender gaps in entrepreneurial intentions among our nation's teens?

Abstract: PurposeThe purpose of this paper is to examine the reasons behind the significant gender gaps observed in entrepreneurial interest among adolescents. Specifically, the authors aim to test multiple models that analyze direct and indirect relationships between work and leadership experience, presence of a parental role model, self‐efficacy, and interest by teens in becoming entrepreneurs.Design/methodology/approachA sample of over 5,000 middle and high school students participated in the larger study from which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
153
1
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(198 citation statements)
references
References 22 publications
17
153
1
12
Order By: Relevance
“…This means that low levels of self-efficacy, resulting from the perceived absence of necessary skills and abilities, influence females more negatively in terms of entrepreneurial intentions. Thus, self-efficacy plays a more significant role in the entrepreneurial behaviour of females compared to males (Kickul et al, 2008;Bandura et al, 2001). …”
Section: Gender and Entrepreneurshipmentioning
confidence: 99%
“…This means that low levels of self-efficacy, resulting from the perceived absence of necessary skills and abilities, influence females more negatively in terms of entrepreneurial intentions. Thus, self-efficacy plays a more significant role in the entrepreneurial behaviour of females compared to males (Kickul et al, 2008;Bandura et al, 2001). …”
Section: Gender and Entrepreneurshipmentioning
confidence: 99%
“…Similarly, some studies have shown that women reject the idea of starting up a new business due to a perception that they lack the necessary skills (Chen, Greene & Crick, 1998;Kickul, Wilson, Marlino & Barbosa, 2008;Mueller & Conway Dato-On, 2008;Wilson et al, 2007). It should also be taken into account that Athayde (2009) confirmed a higher global score in the ATE among men than women, consequently:…”
Section: Hypothesis 1: Reliability and Validity Indexes Of The Ate Tementioning
confidence: 99%
“…Women have made significant progress in entrepreneurship (Kickul et al, 2008) and it became an important source of employment for women across many countries. The number of female entrepreneurs has increased significantly in recent years but still it is more than obvious that the number of businesses owned by women is remarkably lower than the number of businesses owned by men (Guptaa et al, 2014; Pines et al, 2010).…”
Section: Hyp 22 In Life Goalsmentioning
confidence: 99%